Strengthening of overloaded PRC beams with the combination of CFRP laminates bonding and resin injection. (October 2022) - Zhang, Yaosheng; Wang, Lianguang; Li, Xue
Abstract: The flexural behavior of overloaded PRC beams strengthened with CFRP laminates external bonding and resin injection was investigated in this paper. The influences of the overload amplitude, overload numbers, and the effect of overload after strengthening on the strengthened beams were determined. The failure modes of the test beams were that the concrete was crushed after the CFRP laminates debonded. Resin injection effectively inhibited or delayed the re-cracking of the original concrete cracks. Increasing the overload numbers could increase the stiffness of the strengthening beam but had little effect on the yield load. Increasing the overload amplitude could increase the yield load of the strengthening beam but had little effect on the stiffness. Both the overload amplitude and the overload numbers had little influence on the ductility coefficients of damaged beams. The method of CFRP laminates external bonding and resin injection had no obvious effect on improving the ultimate load of the test beams. In the range of load amplitude from 0.1 P y to 0.9 P y, loading the strengthened damaged beam 100 times will not have a negative impact on the bond performance of CFRP. Based on the strain energy theory and variation principle, a model was proposed to predict the shear stress between the RC beam and CFRP laminates, and the model prediction meets the requirements.